Preparation method of aluminum-doped quartz sand
By adopting nanoscale vapor-phase alumina and vapor-phase silica, combined with high-pressure molding and high-temperature sintering processes, the problems of medium and low density, carbon pollution and difficulty in doping of existing synthetic quartz sand technology are solved, and aluminized doped quartz sand with excellent high purity, high density and high temperature resistance are achieved, which is suitable for high-end fields such as photovoltaics and semiconductors.
Patent Information
- Application Number
- CN202411725915.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-21
AI Technical Summary
The existing synthetic quartz sand technology has problems such as low density, carbon pollution, low hardness and difficulty in doping, and cannot completely replace natural quartz sand, especially in terms of high temperature resistance and uniform distribution of aluminum elements.
Nano-scale vapor-phase alumina and vapor-phase silica are used as raw materials, and aluminum-doped quartz sand with high purity, high density and excellent high temperature resistance are prepared through mixing, high pressure molding, high temperature sintering and other processes. This method improves the uniform distribution of aluminum elements and the transparent sintering effect of quartz sand through the uniform dispersion of nano-scrubber and the granulation process of centrifugal drying spray granulation tower.
It achieves high purity (≥99.999%) and high density of quartz sand, enhances its high temperature resistance, and uniform distribution of aluminum elements. It is suitable for applications in photovoltaics, semiconductors and other fields. It has a simple preparation method and is suitable for mass production.
Smart Images

Figure CN119661207A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of synthetic quartz sand, and in particular to a method for preparing aluminum-doped quartz sand. Background Art
[0002] In recent years, with the continuous development of high-tech fields such as photovoltaics and semiconductors, the requirements for material performance have been increasing, mainly due to the growing demand for high-quality and high-purity quartz sand, especially in high-tech fields such as photovoltaics and semiconductors. As these industries have increasingly higher requirements for material performance, traditional natural quartz sand is difficult to meet the demand due to insufficient purity or unstable composition, which has promoted the development of artificial synthetic quartz sand technology.
[0003] The production of artificial synthetic quartz sand does not rely on natural quartz minerals and can be prepared through chemical processes. Synthetic quartz sand has the characteristics of high purity, controllable composition, and excellent optical properties, which makes it widely used in the field of high-end optics. It also meets the requirements of semiconductor processes for quartz products to be high-purity, pollution-free, and high-temperature resistant.
[0004] In semiconductor chip manufacturing, as the chip line width continues to shrink, the purity requirements for quartz materials are getting higher and higher. Ordinary natural quartz materials can no longer meet the requirements of high-end production processes. Therefore, synthetic quartz sand has become an important alternative material. Another major application of synthetic sand is as a raw material for the inner layer of quartz crucibles to replace imported natural sand. For quartz crucibles, the current industry development trend is large size and high duration. From the general consensus of the current industry, doping high-purity quartz sand with an appropriate amount of aluminum can slow down the crystallization of quartz products under high temperature conditions, thereby enhancing the high temperature resistance of quartz crucibles or other quartz products.
[0005] At present, the technical route of synthetic sand is still in the exploratory stage, which can be roughly divided into three types: the first route is to use organosilane as raw material to prepare amorphous silica by sol-gel method, such as patents CN 116924415A, CN116375040 A, etc.; the second route is mainly to use high-purity silica gel solution as raw material, and obtain amorphous silica by dehydration process, such as patent CN 110255570 A, etc.; the third route is also to use organosilane or silicon tetrachloride as raw material, and obtain amorphous silica by vapor deposition. After that, the amorphous silica is subjected to particle size shaping, drying, calcination, and purification to obtain high-purity synthetic fused quartz sand, such as patent CN 116375315 A, etc. Through these three technical routes, transparent synthetic fused quartz sand can be obtained in theory, but there are a series of problems such as low density, carbon pollution, low hardness, and difficulty in doping of synthetic sand, which cannot completely replace natural sand in practical applications.
[0006] In addition, there are many studies on aluminum doping of quartz sand. For example, patents CN109467306A and CN112299864A, etc., mix aluminum-containing substances with natural sand after treatment. The aluminum added by this method can only adhere to the surface of quartz sand, and the aluminum element is not evenly distributed in the quartz sand, which will deteriorate the high temperature resistance of the quartz crucible. Patent CN114044520A mixes aluminum-containing substances in the preparation process of synthetic quartz sand precursor to achieve the purpose of aluminum doping. However, this method will introduce other anions into the quartz sand, affecting the final purity of the quartz sand. Summary of the invention
[0007] In view of the deficiencies in the prior art, the present invention provides a method for preparing aluminum-doped quartz sand. Nanoscale fumed alumina and fumed silicon dioxide are used, and the aluminum-doped quartz sand with excellent performance is obtained through mixing, high-pressure molding, high-temperature sintering and other processes. The purity is ≥99.999%, the density is high and the temperature resistance is excellent. The aluminum content is controllable and evenly distributed, which can meet the requirements of photovoltaic, semiconductor and other fields for high purity and high temperature resistance of quartz sand. The preparation method is simple and suitable for mass production.
[0008] In order to solve the above technical problems, the present invention provides a method for preparing aluminum-doped quartz sand, comprising the following steps:
[0009] S1, dispersing fumed alumina, fumed silica, a dispersant, a defoaming agent and a binder in ultrapure water to obtain a mixed solution, and uniformly dispersing the solution for 2-5 hours using a nano-grinding machine to form a milky suspension having a solid content of 40wt%-60wt%;
[0010] S2, using a centrifugal drying spray granulation tower to spray granulate the suspension to form spherical particles of 20-200 μm;
[0011] S3, mixing the spherical particles with a release agent, and pressing and molding the mixture using a cold isostatic pressing device to obtain a molded body;
[0012] S4, subjecting the molded body to high-temperature binder removal treatment, and then heating to 1200-1500° C. and sintering for 2-8 hours to perform transparent treatment to obtain an aluminum-doped transparent quartz body, and crushing to obtain 40-250 mesh aluminum-doped quartz sand.
[0013] The invention uses nanometer-sized high-purity gas-phase alumina and high-purity gas-phase silica as raw materials, which are easy to obtain and have no carbon pollution. Different from the sol-gel method using organic silane as raw material and alcohol as solvent, the invention greatly reduces the introduction of carbon impurities and improves the purity of quartz sand. The gas-phase alumina is used as an aluminum source, mixed with gas-phase silica through liquid phase, and ground with a high-speed nano sand mill to improve the uniformity of aluminum element dispersion. Spherical particles are formed by a centrifugal drying spray granulation tower to improve the sintering activity of the particles, and cold isostatic pressing is used to discharge the interstitial gas of the spherical particles, reduce the volume shrinkage ratio before and after sintering, and reduce the quartz sand transparent sintering temperature, so as to achieve a sintered body that is completely transparent and free of bubble defects. The sand making method of first forming and then crushing can prepare synthetic quartz sand products with different specifications and different particle size distributions to meet various requirements of different processes for quartz sand particle size distribution.
[0014] Furthermore, in S1, the particle size of the fumed alumina is 10-100 nm and the purity is 99.9999%;
[0015] And / or, the particle size of the fumed silica is 50-200 nm and the purity is 99.9999%;
[0016] And / or, the addition amount of the fumed alumina is 1-10 ppm of the total mass of the fumed alumina and the fumed silica.
[0017] Furthermore, in S2, the process parameters of the spray granulation are: atomizing disk speed 2000-10000 rpm, air inlet temperature 120-250°C, and air outlet temperature 50-150°C.
[0018] Furthermore, in S3, the working pressure of the press molding is 20-200 MPa, and the holding time is 1-10 min.
[0019] Furthermore, in S4, the temperature of the high temperature debinding treatment is 600-800° C., and the time is 4-10 hours.
[0020] Furthermore, the dispersant is one or more of polyethylene glycol, triethylhexyl phosphoric acid, and polyacrylamide.
[0021] Furthermore, the defoaming agent is one or more of silicone, polydimethylsiloxane, and polyether-modified polysiloxane.
[0022] Furthermore, the binder is one or more of polyvinyl alcohol, polypropylene alcohol and silica sol.
[0023] Furthermore, the total mass of the dispersant, defoamer and binder is 0.1%-0.5% of the mass of the mixed solution.
[0024] Furthermore, the release agent is one or more of silicone oil, polyethylene glycol, and polyethylene;
[0025] And / or, the added amount of the release agent is 0.1%-0.5% of the mass of the spherical particles.
[0026] Beneficial effects of the present invention:
[0027] The present invention uses nano-sized high-purity fumed alumina and high-purity fumed silica as raw materials, which are easily available and have no carbon pollution. Different from the sol-gel method using organic silane as raw material and alcohol substances as solvent, the invention greatly reduces the introduction of carbon impurities and improves the purity of quartz sand. The purity of quartz sand is ≥99.999%.
[0028] The present invention uses fumed alumina as an aluminum source, mixes it with fumed silicon dioxide through a liquid phase, and grinds it with a high-speed nano sand mill to improve the uniformity of aluminum element dispersion, thereby improving the uniformity of aluminum element distribution in quartz sand.
[0029] The present invention forms spherical particles through a centrifugal drying spray granulation tower to improve the sintering activity of the particles, and discharges the interstitial gas of the spherical particles through cold isostatic pressing to reduce the volume shrinkage ratio before and after sintering, thereby reducing the sintering temperature of quartz sand transparency, achieving a sintered body that is completely transparent and free of bubble defects, and the quartz sand has high density and excellent temperature resistance.
[0030] The present invention can prepare synthetic quartz sand products with different specifications and different particle size distributions through a sand making method of first forming and then crushing, thereby meeting various requirements of different processes for quartz sand particle size distribution. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solution of the present invention, the drawings required for use in the embodiments are briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 is an optical photograph of aluminum-doped quartz sand prepared in Example 1 of the present invention;
[0033] Figure 2 This is an optical photograph of aluminum-doped quartz sand prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0034] The technical solution of the present invention will be described clearly and completely below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] This embodiment provides a method for preparing aluminum-doped quartz sand, comprising the following steps:
[0036] S1, dispersing fumed alumina, fumed silica, a dispersant, a defoaming agent and a binder in ultrapure water to obtain a mixed solution, and uniformly dispersing the solution using a nano-grinding machine to form a milky suspension having a solid content of 40wt%-60wt%;
[0037] The particle size of the fumed alumina is 10-100 nm, and the purity is 99.9999%; the particle size of the fumed silica is 50-200 nm, and the purity is 99.9999%; the addition amount of the fumed alumina is 1-10 ppm of the total mass of the fumed alumina and the fumed silica;
[0038] S2, using a centrifugal drying spray granulation tower to spray granulate the suspension to form spherical particles of 20-200 μm;
[0039] The process parameters of the spray granulation are: atomizing disk speed 2000-10000rmp, air inlet temperature 120-250°C, air outlet temperature 50-150°C;
[0040] S3, mixing the spherical particles with a release agent, and pressing and molding the mixture using a cold isostatic pressing device to obtain a molded body;
[0041] The working pressure of the pressing process is 20-200 MPa, and the holding time is 1-10 min.
[0042] S4, subjecting the molded body to a high-temperature binder removal treatment, and then heating it to 1200-1500° C. and sintering it for 2-8 hours to perform a transparent treatment to obtain an aluminum-doped transparent quartz body, and crushing it to obtain 40-250 mesh aluminum-doped quartz sand;
[0043] Wherein, the temperature of the high-temperature debinding treatment is 600-800°C and the time is 4-10h.
[0044] As a specific example, the dispersant is one or more of polyethylene glycol, triethylhexyl phosphoric acid, and polyacrylamide; the defoaming agent is one or more of silicone, polydimethylsiloxane, and polyether-modified polysiloxane; the binder is one or more of polyvinyl alcohol, polypropylene alcohol, and silica sol; the total mass of the dispersant, defoaming agent, and binder is 0.1%-0.5% of the mass of the mixed solution.
[0045] As a specific example, the release agent is one or more of silicone oil, polyethylene glycol, and polyethylene; the added amount of the release agent is 0.1%-0.5% of the mass of the spherical particles.
[0046] The following are specific embodiments.
[0047] Example 1
[0048] This embodiment relates to a method for preparing aluminum-doped quartz sand, comprising the following steps:
[0049] (1) 10 g of fumed alumina was fully dispersed in 1 kg of ultrapure water to form solution A, 20 g of solution A, 20 kg of fumed silica and 30 kg of ultrapure water were stirred and mixed, and 10 g of polyethylene glycol, 15 g of polydimethylsiloxane and 15 g of silica sol were added, and dispersed in a nano sand mill for 2 hours;
[0050] (2) Granulation was performed using a centrifugal drying spray tower, with the atomizing disk speed set to 5000 rpm, the inlet air temperature to 150°C, and the outlet air temperature to 80°C, to form spherical particles of 20 to 200 μm;
[0051] (3) Add 10 g of silicone oil to the collected spherical particles and mix them thoroughly using a three-dimensional mixer for 1 h;
[0052] (4) The mixed spherical particles are placed in a mold and pressed into a number of discs with a size of D300 mm*T10 mm in an isostatic pressing device. The cold isostatic pressing working pressure is 160 MPa and the holding time is 2 min.
[0053] (5) debinding at 650° C. for 6 hours, heating to 1200° C. for sintering and transparency, and sintering for 6 hours to form an aluminum-doped transparent quartz body;
[0054] (6) crushing the aluminum-doped transparent quartz body into aluminum-doped quartz sand with a particle size of 60-160 mesh.
[0055] Example 2
[0056] This embodiment relates to a method for preparing aluminum-doped quartz sand, comprising the following steps:
[0057] (1) 10 g of fumed alumina was fully dispersed in 1 kg of ultrapure water to form solution A, 40 g of solution A, 20 kg of fumed silica and 30 kg of ultrapure water were stirred and mixed, and 12 g of polyethylene glycol, 16 g of polydimethylsiloxane and 13 g of silica sol were added, and dispersed in a nano sand mill for 3 hours;
[0058] (2) Granulation was performed using a centrifugal drying spray tower, with the atomizing disk speed set to 6500 rpm, the inlet air temperature to 180°C, and the outlet air temperature to 100°C, to form spherical particles of 50-250 μm;
[0059] (3) Add 13 g of silicone oil to the collected spherical particles and mix thoroughly for 1.5 h using a three-dimensional mixer;
[0060] (4) The mixed spherical particles are placed in a mold and pressed into a number of discs with a size of D300 mm*T10 mm in an isostatic pressing device. The cold isostatic pressing working pressure is 120 MPa and the holding time is 4 min.
[0061] (5) debinding at 800° C. for 4 hours, heating to 1250° C. for sintering and transparency, and sintering for 4 hours to form an aluminum-doped transparent quartz body;
[0062] (6) crushing the aluminum-doped transparent quartz body into aluminum-doped quartz sand with a particle size of 80-200 mesh.
[0063] Test Case
[0064] The optical photographs of the aluminum-doped quartz sand prepared in Example 1 and Example 2 are shown in FIG. Figure 1 and Figure 2 As shown, it can be seen that the synthetic sand particles prepared by the method of the present invention are completely transparent and free of bubble defects, and the particle size distribution range of the synthetic sand is concentrated.
[0065] The impurity conditions, aluminum content and purity of silicon dioxide (SiO2) of the aluminum-doped quartz sand prepared in Example 1 and Example 2 are shown in Table 1. It can be seen that the aluminum-doped quartz sand prepared by the method of the present invention has a purity of more than 99.999%, a low impurity content, and excellent high temperature resistance.
[0066] Table 1
[0067]
[0068] In summary, the present invention uses nano-sized high-purity gas-phase alumina and high-purity gas-phase silica as raw materials. The raw materials are easy to obtain and have no carbon pollution. Different from the sol-gel method using organic silane as raw material and alcohol substances as solvent, the introduction of carbon impurities is greatly reduced, and the purity of quartz sand is improved; gas-phase alumina is used as an aluminum source, mixed with gas-phase silica through the liquid phase, and ground with a high-speed nano sand mill to improve the uniformity of aluminum element dispersion; spherical particles are formed through a centrifugal drying spray granulation tower to improve the sintering activity of the particles, and cold isostatic pressing is used to discharge the interstitial gas of the spherical particles, reduce the volume shrinkage ratio before and after sintering, and reduce the quartz sand transparent sintering temperature, so as to achieve a sintered body that is completely transparent and free of bubble defects; through the sand making method of first forming and then crushing, synthetic quartz sand products with different specifications and different particle size distributions can be prepared to meet various requirements of different processes for quartz sand particle size distribution.
[0069] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing aluminum-doped quartz sand, characterized in that: The steps include: S1, dispersing fumed alumina, fumed silica, a dispersant, a defoaming agent and a binder in ultrapure water to obtain a mixed solution, and uniformly dispersing the solution using a nano-grinding machine to form a milky suspension having a solid content of 40wt%-60wt%; S2, using a centrifugal drying spray granulation tower to spray granulate the suspension to form spherical particles of 20-200 μm; S3, mixing the spherical particles with a release agent, and pressing and molding the mixture using a cold isostatic pressing device to obtain a molded body; S4, subjecting the molded body to high-temperature binder removal treatment, and then heating to 1200-1500° C. and sintering for 2-8 hours to perform transparent treatment to obtain an aluminum-doped transparent quartz body, and crushing to obtain 40-250 mesh aluminum-doped quartz sand.
2. The method for preparing aluminum-doped quartz sand according to claim 1, characterized in that: In S1, the particle size of the fumed alumina is 10-100 nm and the purity is 99.9999%; And / or, the particle size of the fumed silica is 50-200 nm and the purity is 99.9999%; And / or, the addition amount of the fumed alumina is 1-10 ppm of the total mass of the fumed alumina and the fumed silica.
3. The method for preparing aluminum-doped quartz sand according to claim 1, characterized in that: In S2, the process parameters of the spray granulation are: atomizing disk speed 2000-10000 rpm, air inlet temperature 120-250°C, and air outlet temperature 50-150°C.
4. The method for preparing aluminum-doped quartz sand according to claim 1, characterized in that: In S3, the working pressure of the compression molding is 20-200 MPa, and the holding time is 1-10 min.
5. The method for preparing aluminum-doped quartz sand according to claim 1, characterized in that: In S4, the temperature of the high temperature debinding treatment is 600-800°C and the time is 4-10 hours.
6. The method for preparing aluminum-doped quartz sand according to claim 1, characterized in that: The dispersant is one or more of polyethylene glycol, triethylhexyl phosphoric acid and polyacrylamide.
7. The method for preparing aluminum-doped quartz sand according to claim 1, characterized in that: The defoaming agent is one or more of organic silicon, polydimethylsiloxane and polyether modified polysiloxane.
8. The method for preparing aluminum-doped quartz sand according to claim 1, characterized in that: The binder is one or more of polyvinyl alcohol, polypropylene alcohol and silica sol.
9. The method for preparing aluminum-doped quartz sand according to claim 1, characterized in that: The total mass of the dispersant, defoamer and binder is 0.1%-0.5% of the mass of the mixed solution.
10. The method for preparing aluminum-doped quartz sand according to claim 1, characterized in that: The release agent is one or more of silicone oil, polyethylene glycol, and polyethylene; And / or, the added amount of the release agent is 0.1%-0.5% of the mass of the spherical particles.
Citation Information
Patent Citations
Method for processing high-strength quartz crucible for monocrystalline silicon production
CN109467306A
Modified fused quartz sand and preparation process thereof
CN112299864A
Preparation method of high-aluminum ultrapure synthetic quartz sand
CN114044520A
6N-grade large-particle quartz sand and preparation method thereof
CN116375040A
Preparation method of ultra-high-purity quartz sand
CN116924415A
Cited By
Preparation method of aluminum-doped synthetic quartz sand
CN121317768A